LITERASI SEKOLAH SEBAGAI STRATEGI PEMBENTUKAN GEMAR MEMBACA PADA SISWA SEKOLAH DASAR - Nur Ilami; Dewi Hosnul Khotimah Khomaeroh; Musdalifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the role of school literacy in forming the character of reading in elementary school students through a literature study approach. This research uses a qualitative approach with the library research method. The results of the study show that the implementation of school literacy consisting of routine reading activities, the provision of reading corners, and teacher assistance contributes significantly to fostering interest and reading habits in students. The integration of conventional and digital literacy enriches students’ learning experiences while improving critical thinking, communication, and digital skills as demands of 21st century learning. Family support and school policies are also important factors in creating a sustainable literacy ecosystem. This study emphasizes that literacy not only functions to improve reading skills but also acts as an instrument for character formation that is disciplined, independent, and has high curiosity.